Original paperExperimental study of the to cytotoxic effects of neutrophils on chondrocytes cultivated in different oxygen concentrations - Gajewski, Michał; Warnawin, Ewa; Gajewska, Joanna; Sygitowicz, Grażyna; Rell-Bakalarska, Maria; Burakowski, Tomasz; Dziewczopolski, Wojciech; Szczepanik, Szymon; Wysocki, Łukasz; Pachecka, Jan; Maśliński, Włodzimierz; Maśliński, Sławomir (Reumatologia/Rheumatology, 2006)
The main objective of our work was to examine how different oxygen levels affects cytotoxic interactions between human neutrophils and chondrocytes obtained from the cartilage. We studied the connections between neutrophils activation (CL) and the availability of glucose, the amount of energy and the activity of the penthose phosphate pathway. We found that NADPH oxidase affects the intensity of the inflammation process but the amount of energy (ATP) had no direct influence on neutrophils activation. Chondrocytes cultivation in different oxygen conditions demonstrated that although in high oxygen levels (21%), the survival of the cells being in hyperoxia- state varies not from cells cultivated in low oxygen conditions, they are significantly more exposed to the toxic influence of neutrophils. The inactivation of NADPH production, noticeably lowering the level of damage delivered to the chondrocytes, could suggest that a blocker of this pathway (DOG) might be a useful remedy, reducing the intensity of the inflammation process.